VALIDITY AND PRACTICALLY OF MODIFIED FLASHCARD MEDIA OF INTERACTION AMONG LIVING THINGS MATERIAL FOR MTS STUDENTS - Qurrotul Uyuni; Nur Kuswanti (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2022)
Students in one of the Islamic junior high schools (MTs) in Jombang are better able to understand science material by using visual learning media. One of the science materials that requires visual media is the interaction between living things. This was a development research. The general purpose of this study was to develop modified flashcards as learning media for junior high school on the material of interaction among living things. Meanwhile, the main purposes were to describe the process and results of developing the media. This research used the ADDIE development model which stands for Analize, Design, Development, Implementation, and Evaluation. The modified flashcard media after being developed was then examined for their validity and practicality. The results of the analysis showed that the modified flashcard media on the interaction material among living things obtained averages of validity score of 3.6 and practicality score of 3.83. Based on these results, the developed media belongs to the category of very valid and very practical.